2015
DOI: 10.1590/s0080-623420150000200012
|View full text |Cite
|
Sign up to set email alerts
|

Scientific production on workplace bullying/harassment in dissertations and theses in the Brazilian scenario

Abstract: Objective:To analyze scientific production about workplace bullying and harassment in dissertations and theses in Brazil, with emphasis on the year of publication; educational institution; area of knowledge; professional and academic background of the authors; keywords used; and concept map organization. Method: Bibliometric study with a quantitative approach with a sample consisting of 57 papers, 5 theses and 52 dissertations, published between 2002 and 2012. Results: It was found that 2012 was the year with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
2
8
0
3
Order By: Relevance
“…Intensive Care Units came from the South and Southeast regions. This finding is similar to the results of bibliometric research on moral harassment in the Brazilian scenarios, whose results indicate that 84.2% of theses and dissertations on this theme come also from the South and Southeast (14) . The predominance of these regions may be due to their pioneering nature in offering strictu sensu courses (13) .…”
Section: The Largest Number Of Publications About Adultsupporting
confidence: 88%
“…Intensive Care Units came from the South and Southeast regions. This finding is similar to the results of bibliometric research on moral harassment in the Brazilian scenarios, whose results indicate that 84.2% of theses and dissertations on this theme come also from the South and Southeast (14) . The predominance of these regions may be due to their pioneering nature in offering strictu sensu courses (13) .…”
Section: The Largest Number Of Publications About Adultsupporting
confidence: 88%
“…This reality is confirmed by a bibliometric study approaching dissertations and theses in national settings. This study showed that, among 57 studies analyzed, 12 resulted in studies published in journals (18) . It is understood that the publication of these studies is of utmost importance for the dissemination of research results.…”
Section: Discussionmentioning
confidence: 81%
“…Studies show that it is necessary to guarantee the safety of health workers in order to prevent injuries, leave and abandonment of employment, as well as social isolation and the intention to quit work ( 14 , 28 ) .…”
Section: Discussionmentioning
confidence: 99%